The Influence of Transportation Infrastructure on Community Economic Improvement in Makassar Island, Baubau City - Novianti, Novianti; Rizal, Erliani (Jurnal Indonesia Sosial Teknologi, 2024)
Makassar Island is an island area in Baubau City, Southeast Sulawesi Province which is included in the Kokalukuna District. It consists of two villages, namely Liwuto Village and Sukanayo Village with a land area of 1.04 km2. In general, 70% of the livelihood of residents on Makassar Island is fishing, seaweed farming, pearl oysters, fish marketing businesses, and crossing services (sea taxis). As an island area, the movement of both goods and people within this region is closely related to the infrastructure of docks and highways. This study aims to analyze the influence of transportation infrastructure in improving the economy of the people on Makassar Island. The analysis methods used in this study are Likert analysis, correlation analysis and simple linear regression analysis. Based on the results of the analysis, it was found that transportation infrastructure has a strong relationship with the community’s economy. Furthermore, the results of the study are presented in the form of a crosstab between each indicator of the transportation infrastructure variable (X) with the economic variable of the community (Y) on the island.